Mastery of Aesthetic and Functional Restoration of Maxillary Molars Using the Technique of Direct Restoration (Clinical Case) - Kolenko, Ю. Г.; Volovyk, І. А.; Kardash, А. О. (Actual Dentistry, 2025)
Relevance. Hublishing articles about clinical cases plays an important role, occupies a specific position, and has its purpose in modern medical science and education. Writing articles on clinical cases is especially relevant for students and young scientists, as they are often their first step in the vast journalistic world of medical science. Aim: increase the effectiveness of the educational process through the practical implementation of theoretical knowledge and clinical thinking in the diagnosis and treatment of gingivitis and caries by creating direct artistic restorations of molars to restore the aesthetics and functionality of the dentition. Material and methods. Students of the Faculty of Dentistry of the Bogomolets National Medical University, under the mentoring of the scientific supervisor of the Department of Therapeutic Dentistry, conducted a comprehensive examination and created a treatment and prevention program for patient K., who applied for oral cavity rehabilitation in December 2024. Patient K., 22 years old, female, student, Kyiv. Research methods: clinical, laboratory (radiological), empirical. Results. According to the results of clinical examination methods, the caries intensity index of the checkpoint was 15, which corresponds to a high level. The O’Leary oral hygiene level was 92%. The results of basic periodontal screening: BOP bleeding index 81%, PPD < 3.5 mm, PSR: code 2. The results of an empirical study (questionnaire) revealed a low level of medical dental awareness. The primary individual risk factors for caries and periodontal tissue diseases of local and general significance were analyzed. Based on the results of clinical and X-ray examination methods, the following diseases were diagnosed: ‘Caries’ of 17, 16, 15 teeth and ‘Gingivitis induced by dental biofilm’. A personalized, comprehensive treatment and prevention program plan was drawn up following modern treatment protocols. Conclusions. It is recommended that students actively involve themselves in developing clinical skills during practical training. This significantly increases the efficiency of the educational process at the university and allows it to become more competitive in the professional environment.